Influence of environmental temperature on mouth‐form plasticity in Pristionchus pacificus acts through daf‐11‐dependent cGMP signaling. Issue 2 (11th August 2021) - Lenuzzi, Maša; Witte, Hanh; Riebesell, Metta; Rödelsperger, Christian; Hong, Ray L.; Sommer, Ralf J.
Abstract: Mouth‐form plasticity in the nematode Pristionchus pacificus has become a powerful system to identify the genetic and molecular mechanisms associated with developmental (phenotypic) plasticity. In particular, the identification of developmental switch genes that can sense environmental stimuli and reprogram developmental processes has confirmed long‐standing evolutionary theory. However, how these genes are involved in the direct sensing of the environment, or if the switch genes act downstream of another, primary environmental sensing mechanism, remains currently unknown. Here, we study the influence of environmental temperature on mouth‐form plasticity. We find that environmental temperature does influence mouth‐form plasticity in most of the 10 wild isolates of P. pacificus tested in this study. We used one of these strains, P. pacificus RSA635, for detailed molecular analysis. Using forward and reverse genetic technology including CRISPR/Cas9, we show that mutations in the guanylyl cyclase Ppa‐daf‐11, the Ppa‐daf‐25 /AnkMy2, and the cyclic nucleotide‐gated channel Ppa‐tax‐2 eliminate the response to elevated temperatures. Together, our study indicates that DAF‐11, DAF‐25, and TAX‐2 have been co‐opted for environmental sensing during mouth‐form plasticity regulation in P. pacificus . Abstract : Ppa‐daf‐11 expression in five amphid neurons involved in temperature perception. Research Highlights: Mouth‐form plasticity in Pristionchus is temperature dependent. Mutations daf‐11/guanylyl cyclase, daf‐25/AnkMy2, and tax‐2/cyclic nucleotide‐gated channel eliminate this response, suggesting that plasticity requires perception by cGMP signaling.